From theory to practice: A worldwide cross-sectional survey about flywheel training in basketball - Younes-Egaña, O.; Bird, S. P.; Calleja-González, J. (International Journal of Sports Physiology and Performance, 2023)
Purpose This study aimed to comprehensively investigate the global implementation of flywheel training (FT) by basketball strength and conditioning (S&C) coaches in various contexts, encompassing daily practice, games, and sessions. Methods Survey data were collected from 117 basketball S&C coaches who participated in a 24-question online survey. The survey was structured into 6 key areas, including country and competition, S&C coach context, training methodology, flywheel and competition, postactivation performance enhancement, and recovery. Results Notably, all respondents emphasized the necessity of a familiarization period with flywheel technology, with a substantial 96% indicating that FT yielded improved player performance on the court. The predominant mention was the conical pulley system. During the season, the prevalent approach involved integrating FT into training twice a week, allocating <15 minutes per session, often in conjunction with traditional strength training. A diverse array of lower-body closed kinetic chain exercises were reported, encompassing squats, decelerations, and backward lunges. Intriguingly, FT implementation on match days was unlikely (77%), with the primary aims cited as injury prevention (34%) and enhancing players` strength levels during various phases of the regular season (27%). Conclusions Recognizing its inherent limitations, this descriptive study provides valuable contextual insights and practical applications for professional basketball practitioners grappling with the utilization of FT.